Impact of intellectual capital on financial performance of the Indian software sector / Deepika Bansal and Shveta Singh - Bansal, Deepika; Singh, Shveta (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2020)
The purpose of the study was to analyse and examine the effect of intellectual capital on profitability and productivity of the Indian software sector. An empirical investigation was done on 71 software companies. Data for the study was collected from the CMIE prowess database for the period of five years from 2013 to 2018. The Value Added Intellectual Coefficient (VAIC) Model was used for the measurement of intellectual capital (IC) and its components. The Pearson and Panel Regression Model was used for the analysis of data. The findings show that, varying relationships exist between intellectual capital components and financial performance measures such as profitability and productivity. Findings of the study also suggest that VAIC, positively and significantly explains profitability of the companies but not productivity. Intellectual capital is an interesting area for all the parties like managers, shareholders, government, institutional investors, policy makers etc. This study increases the knowledge of all parties about the impact of intellectual capital on performance of concerned companies. The results of the study can be utilised for the enhancement of productivity and profitability of companies by a proper management of intellectual capital